Participative disaster management: Post-disaster renewal of Palu City - Sofyan, Imam; Erdiyansyah,; Moh. Royfandi, (Technium Social Sciences Journal, 2020)
The potential for disasters in Indonesia is high and especially in Palu City, which an area with very frightening natural disasters such as earthquakes, tsunamis and liquefaction. This disaster has occurred in Palu City, so the government and its people need to be prepared to face it. Based on this, this study investigates the steps of the Palu City government in participatory urban renewal involving the post-disaster community. This research was designed qualitatively with a phenomenological approach. The results showed that the government has taken steps and reformed Palu City through post-disaster development that occurred on September 28, 2018. In this participatory development, the Palu City government carried out several stages of disaster management activities including pre-disaster, emergency response, and post-disaster. Disaster management involves various stakeholders, but the research results show that the government has not yet involved the community at every stage of disaster management. The three stages of disaster management, the last stage is that involves the community in carrying out urban renewal, but this not visible. The impact is that the community it’s not satisfied with the development policies of the Palu City government, in which the government does not synergize with the community so the goal of reforming through participatory development policies not achieved